Paracoccidioidomycosis of external genitalia: report of six new cases and review of the literature Paracoccidioidomicose de localização genital externa: relato de seis novos casos e revisão da literatura - Silvio Alencar Marques; Lilian Kanawa Tangoda; Rosangela Maria Pires de Camargo; Hamilton Ometto Stolf; Mariangela Esther Alencar Marques (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Paracoccidioidomycosis is a systemic mycosis of dermatological interest due to the frequency of cutaneous and mucosal lesions. The involvement of the external genitalia is extremely rare and few cases have been reported. OBJECTIVE: To study the prevalence of external genitalia lesions in paracoccidioidomycosis patients, identify clinical characteristics and compare with what is observed in the specific literature. METHODS: This is a cross-sectional, descriptive study, with focus on paracoccidioiodomycosis patients with external genitalia lesions. The demographic and clinical aspects of cases were compared with what has been reported so far on LILACS, SciELO e MEDLINE data bases. RESULTS: Data of 483 cases of paracoccidioidomycosis were studied in a 42-year period. Six (1.2%) patients showed specific lesions on external genitalia. Five patients were male with mean age of 47.2 years and all of them presented with the chronic multifocal clinical form. Only one, a 15-year-old female patient was observed who showed a subacute clinical form, juvenile type. CONCLUSION: Compromise of the genitourinary tract among paracoccidioidomycosis patients is rare and even rarer when only the external genitalia are considered. As observed in the classical picture of paracoccidioidomycosis patients, the male gender and the chronic multifocal clinical form prevailed in the present study. FUNDAMENTOS: Paracoccidioidomicose é micose sistêmica de interesse dermatológico pela freqüência de lesões tegumentares. Sua localização em genitália externa é extremamente rara e pouco descrita. OBJETIVOS: estudar a prevalência de lesões de paracoccidioidomicose de localização genital, identificar suas características clínicas e compará-las com a literatura específica. MÉTODOS: estudo descritivo, transversal, de série de casos, com inclusão de casos com lesões específicas de paracoccidioidomicose de localização genital externa, estudo das características demográficas e clínicas dos casos, confrontados com dados de revisão da literatura nas bases LILACS, SciELO e MEDLINE. RESULTADOS: foram revisados de 483 pacientes de paracoccidioidomicose diagnosticados no período de 42 anos. Seis (1,2%) pacientes apresentavam lesão específica de genitália externa. Cinco eram do sexo masculino com idade média de 47,2 anos e todos com a forma crônica multifocal da doença, O único caso do sexo feminino, de 15 anos de idade, apresentava a forma subaguda, tipo juvenil. CONCLUSÕES: o comprometimento do trato geniturinário na paracoccidioidomicose é raro e mais ainda quando se considera apenas as localizações de genitália externa. Como na paracoccidioidomicose clássica, o sexo masculino e a forma crônica da doença predominaram na amostragem estudada.